The Use of Instagram in Improving Recount Text Writing Ability: A Study of Nursing Students - Desmiyanti (JURNAL INOVASI EDUKASI, 2023)
The potential of Instagram continues to show an increase in users from year to year. This article is motivated by the anxiety of using Instagram in improving recount text writing skills among nursing students. However, not many lecturers utilise Instagram for learning in lectures. Therefore, this article has an urgency to examine the potential utilisation of Instagram in learning to write recount text. The purpose of this research is to explore various relevant studies and literature related to the topic. The method used is a literature study, using literature sources to find out the potential and use of the media. The result of this study is that the potential of Instagram in learning to write is huge, supported by the number of students using Instagram in their activities. In addition, the use of Instagram in improving recount text writing skills has shown real results. The various features available in the media are very supportive for recount text writing activities for nursing students. The conclusion of this study is that improving writing skills with Instagram is very relevant to the competencies needed by nursing students, namely in writing clinical reports, communication, and their professionalism in the future world of work. keywords: instagram, writing skills, recount text, nursing students